2022
DOI: 10.5758/vsi.210062
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Midline Catheters with Integrated Wire Accelerated Seldinger Technique

Abstract: Purpose The midline catheter (MC) is a peripheral venous access device with the catheter tip located in the axilla and available for mid-term intravenous (IV) therapy. This study evaluated the efficacy and clinical outcomes associated with the placement of MCs with an integrated wire-accelerated Seldinger technique for IV access. Methods Materials and A retrospective review was conducted at a single center in South Korea between March 2020 and July 2020. Consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Chopra, Kaatz, Swaminathan et al [8] in a study of 1161 catheters report such an indication in 61% of the cases examined. In such situations, obtaining vascular access using ultrasound is recommended by the Infusion Nurses Society, as it increases the likelihood of success during the first attempt [9][10][11]. This is supported by the experience of our team, which achieved 92% successful access and reports by other authors whose success rates were between 86 and 100% [2,7,[12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Chopra, Kaatz, Swaminathan et al [8] in a study of 1161 catheters report such an indication in 61% of the cases examined. In such situations, obtaining vascular access using ultrasound is recommended by the Infusion Nurses Society, as it increases the likelihood of success during the first attempt [9][10][11]. This is supported by the experience of our team, which achieved 92% successful access and reports by other authors whose success rates were between 86 and 100% [2,7,[12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 55%
“…It must be noted that in the results presented, complications in the form of catheter obstruction occurred in 36% of the cases, which is more than the data reported in the literature, according to which, this problem affects between 2 and 27% of cases [7][8]10,12,21]. It seems that some reasons for this difference could have been: the overall poor quality of vascular access care, staff shortages, work overload during the pandemic, or insufficient centre Tab.…”
Section: ) the Incidence Of Catheter Obstructionmentioning
confidence: 55%
“…Chopra, Kaatz, Swaminathan et al found such an indication in 61% of the cases examined [2]. Obtaining vascular access using ultrasound in difficult access is recommended by the Infusion Nurses Society due to the higher success rate of this method during the first attempt [3,4]. According to the recommendation of the Society of Hospital Medicine, peripheral access under ultrasound can be an alternative to central catheters used for the same purpose [5].…”
Section: Discussionmentioning
confidence: 99%
“…wskazują takie wskazanie w 61% [2]. Uzyskanie dostępu naczyniowego przy użyciu ultrasonografii w trudnym dostępie jest zalecane przez Infusion Nurses Society, z powodu większej sku-teczności podczas pierwszej próby [3,4]. Według rekomendacji Society of Hospital Medicine dostęp obwodowy pod USG może być alternatywą dla cewników centralnych wykorzystywanych w tym samym celu [5].…”
Section: Dyskusjaunclassified
“…Prior to this study, evidence had been inconclusive and occasionally contradictory when evaluating complication rates between PICCs and midlines 21 22. Midline catheters are gaining traction as a viable replacement for peripheral venous access in patients who have poor intravenous access or require midterm fluid therapy 23. Additional benefits include ease of placement, as they do not require confirmation of tip placement by radiographic or imaging technologies 24.…”
Section: Safety and Outcomes Of Midline Catheters Vs Peripherally Ins...mentioning
confidence: 99%